Ruptured right Valsalva sinus into the right atrium due to infective endocarditis: a case report - Abetti, Ayoub (Pan Afr Med J, 2020)
Rupture of Valsalva sinus remains a very rare and deadly complication of Valsalva sinus aneurysm with a high mortality rate. We report here the case of a 47-year-old man who presented to the emergency department with acute exercise-induced dyspnea, chest pain, and fever. Transthoracic (TTE) and transesophageal echocardiography (TEE) highlighted a rupture of the right Valsalva sinus in the right atrium due to infective endocarditis. After stabilization of the patient, a successful surgical repair with double pericardial patches was performed.